Hubungan Keterampilan Bertanya Guru Dengan Motivasi Belajar Siswa Kelas Tinggi Sekolah Dasar - Muh Idris Jafar; Achmad Sabir; Mutmainna Mutmainna (Universtas Negeri Makassar, 2022)
This research is a correlational study that aims to determine the relationship between teacher questioning skills and high grade students' learning motivation at SDN 28 Pakkita, East Sinjai District, Sinjai Regency. Data analysis techniques are descriptive statistical analysis (mean analysis and percentage analysis) and inferential statistics (normality test, linear test, and hypothesis testing). Based on the results of descriptive statistical analysis, it was obtained that the teacher's questioning skills had an average of 80,96 and a percentage of 80,96% in the very good category, while learning motivation had an average of 83,5 and a percentage of 83,5% in the very good category. The results of inferential statistical analysis on normality testing obtained both research variables that were normally distributed, then in the linear test obtained both data from the research variables were linear, the hypothesis test showed that the rcount value (0,5204) was greater (≥) the rtable value (0,2632) at the 5% significance level. Thus H0 is rejected and H1 is accepted. The conclusion of the study is that there is a significant relationship between the teacher's questioning skills and the learning motivation of high-class students at SDN 28 Pakkita, East Sinjai District, Sinjai Regency.